Gold nanoparticles biosynthesized using Lignosus rhinocerotis extracts: comparative evaluation of biostatic and cytotoxicity effects - Ahmad Yasser Hamdi Nor Azlan,; Haliza Katas,; Nur Qaisara Jalluddin,; Mohd Fauzi Mh Busra, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Gold nanoparticles (AuNPs) are a unique class of nanomaterials applied in biomedical applications. Biological synthesis or biosynthesis of AuNPs offers advantages including simple and cost-effective method as well as nontoxic to human, making it superior to chemical synthesis. In this study, comparative evaluation was conducted for antimicrobial and cytotoxicity effects of chemically synthesized (Chem-AuNPs) and biosynthesized AuNPs (Bio-AuNPs). Chem- and Bio-AuNPs were produced using sodium citrate and L. rhinocerotis extracts, respectively. Different methods namely hot and cold-water extraction (HWE and CWE, respectively) were used to extract L. rhinocerotis sclerotium, a medicinal mushroom. Both types of nanoparticles were stabilized using chitosan (CS) and characterized for their physical characteristics, followed by determination of antibacterial and cytotoxicity effects in vitro. Formation of AuNPs exhibited surface plasmon resonance (SPR) band at 465-564 nm and 523-544 nm for Chem-AuNPs and BioAuNPs, respectively, as determined by UV-vis spectroscopy. CS-stabilized AuNPs had larger size of particles than nonstabilized ones, ranging from 200 to 500 nm. Both Chem- and Bio-AuNPs showed biostatic activity against Grampositive bacteria (Bacillus sp. and Staphylococcus aureus) and Gram-negative bacteria (Pseudomonas aeruginosa and Escherichia coli). The cytotoxicity assay for 24 h showed higher cell viability for Bio-AuNPs than Chem-AuNPs, indicating relatively less toxicity of Bio-AuNPs. In conclusion, Bio-AuNPs using the mushroom extracts and CS provide opportunities for developing stable, safer, and eco-friendly nanoparticles with effective antibacterial properties for clinical applications.